In-situ investigation of hydrogen evolution behavior in vanadium redox flow batteries. (15th March 2017) - Wei, L.; Zhao, T.S.; Xu, Q.; Zhou, X.L.; Zhang, Z.H.
Highlights: An in-situ method to investigate hydrogen evolution in VRFBs is developed. The rate of hydrogen evolution during battery operation is quantified. The gas evolution behaviors in the charge process of VRFBs are observed. Abstract: In this work, we conceived and fabricated a three-electrode electrochemical cell and transparent vanadium redox flow battery to in-situ investigate the hydrogen evolution reaction during battery operation. Experimental results show that operating temperature has a strong influence on the HER rate. In particular, compared with V 3+ reduction reaction, HER is more sensitive to temperature variation. It is also found that, contrary to the conventional wisdom that side reactions occur at the late stage of the charge process, H2 evolves at a relatively low SOC. About 0.26 and 1.94 mL H2 were collected at an early (SOC lower than 20%) and end of the charge process, respectively, suggesting that attention to the hydrogen formation at the negative electrode in the early charge process should also be paid to during long-term battery operations. Moreover, the produced hydrogen gas at the negative side prefers to form macroscopically observable bubbles onto the electrode surface, covering the active sites for vanadium redox reactions, while oxygen evolution (including CO2 production) at the positive side corrodes electrode surface and introduces certain oxygen-containing functional groups.